(untitled) (Physical Education, Health and Social Sciences, 2026)
Background: Pediatric cataract is a significant cause of childhood visual impairment. The presence of strabismus may further compromise the development of normal binocular vision. Objective: To evaluate changes in the pattern and degree of strabismus in pediatric cataract patients before and after cataract surgery. Methods: A quasi-experimental study was conducted over three months on 62 eyes of 31 pediatric cataract patients with ≥10 prism diopters of strabismus, presenting to the Orthoptic Clinic, Mayo Hospital, Lahore. Pre- and postoperative assessments included best-corrected visual acuity (BCVA) using the LogMAR chart, deviation measurement with the Alternate Prism Cover Test (APCT), and cycloplegic refraction using 1% cyclopentolate. Results: Of the 31 patients (54.83% male), the mean age was 7.47 ± 2.60 years for males and 6.71 ± 2.05 years for females. Mean BCVA improved significantly from 0.89 ± 0.09 preoperatively to 0.21 ± 0.06 postoperatively. The mean squint angle decreased from 37.58 ± 7.40 to 28.48 ± 10.00 prism diopters. Postoperatively, 61.29% showed improvement (relieved), 22.58% remained unchanged, 9.68% worsened, and 6.45% developed consecutive deviations. Conclusion: Cataract surgery with intraocular lens (IOL) implantation significantly improves visual acuity and reduces ocular misalignment in pediatric patients. Early surgical intervention can restore vision and enhance binocular coordination.